The Analysis Study of Association Malnutrition and Quality of Life and Outcome of Patients with Chronic Kidney Disease : A Comprehensive Systematic Review - Rahman, Fahmi Fathul; Istiana, Septa (International Medical Journal Corp. Ltd, 2024)
Background: Chronic kidney disease (CKD) is associated with a high risk of morbidity and mortality, and presents a significant public health concern, with increasing incidence and prevalence. CKD can affect an individual’s social, professional and family life. Previous studies have shown that the quality of life (QOL) of patients with CKD is reduced compared to the healthy population. The aim: The aim of this study to show about association malnutrition and quality of life and outcome of patients with chronic kidney disease. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: CKD is associated with decreased QOL as well as significant morbidity and mortality, all of which are amplified in the setting of malnutrition. Nutritional status and monitoring of QOL should be integrated into the standard management guidelines for CKD patients.